2010
DOI: 10.1016/j.ausmj.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Eating Clean and Green? Investigating Consumer Motivations towards the Purchase of Organic Food

Abstract: Growing consumer concern for health and environment issues has resulted in increased attention towards the purchase and consumption of organic food. This has driven an increase in organic research, especially as marketers seek to understand the motivations behind consumer purchases of organic goods. This study explored the effects of health consciousness, environmental concern, organic knowledge, availability, quality, price consciousness, subjective norms, risk aversion, perceived control and familiarity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
306
9
22

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(371 citation statements)
references
References 44 publications
(172 reference statements)
34
306
9
22
Order By: Relevance
“…Product attributes such as quality (Lockie et al, 2002;Smith & Paladino, 2010;Hamzaoui-Essoussi & Zahaf, 2012;Ergin & Ozsacmaci, 2011), better taste (Lockie et al, 2002;Dahm, Samonte, & Shows, 2009;Hasançebi, 2010;Hughner et al, 2007;Stolz, Stolze, Hamm, Janssen, & Ruto, 2010;Hamzaoui-Essoussi & Zahaf, 2012;Ergin & Ozsacmaci, 2011), nutrition value, and freshness (Fotopoulos & Chryssochoidis, 2000) have also found to be influential in organic food consumption.…”
Section: Organic Food Consumption Motivesmentioning
confidence: 99%
“…Product attributes such as quality (Lockie et al, 2002;Smith & Paladino, 2010;Hamzaoui-Essoussi & Zahaf, 2012;Ergin & Ozsacmaci, 2011), better taste (Lockie et al, 2002;Dahm, Samonte, & Shows, 2009;Hasançebi, 2010;Hughner et al, 2007;Stolz, Stolze, Hamm, Janssen, & Ruto, 2010;Hamzaoui-Essoussi & Zahaf, 2012;Ergin & Ozsacmaci, 2011), nutrition value, and freshness (Fotopoulos & Chryssochoidis, 2000) have also found to be influential in organic food consumption.…”
Section: Organic Food Consumption Motivesmentioning
confidence: 99%
“…Furthermore, others have argued that attitude and self identity are interrelated. There are studies which found that individuals who view themselves concerned with environmental issues are more likely to have favorable attitudes towards practicing environmentally responsible behavior (Raisbeck & Wardlaw, 2009;Smith & Paladina, 2010;Pino et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of green products, price and availability have the potential to limit or even prevent individuals' green purchases. Magnusson et al, (2001) and Smith and Paladina (2010) both argued that many individuals consider price to be an important determinant of green purchases. For example, price is often perceived to be a major barrier to the purchase of organic produce (Lea & Worsley, 2005;Magnusson et al, 2001;Michaelidou & Hassan, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the measures employed were: personal values, such as security, fun/enjoyment, and self-gratification (e.g., McCarty & Shrum, 1994;Jansson, Marell, & Nordlund, 2010); ethical ideologies, such as deontologism and teleologism (e.g., Spash, 1997;Chan et al, 2008); societal factors, such as liberalism and social altruism (e.g., Straughan & Roberts, 1999;Paladino, 2005); cultural orientations, such as collectivism and individualism (e.g., Laroche, Bergeron, & Barbaro-Forleo, 1999;McCarty & Shrum, 2001); and personal environmental beliefs, such as faith in others, perceived consumer effectiveness, and susceptibility to normative influence (e.g., Ellen et al,. 1991;Minton & Rose, 1997;Smith & Paladino, 2010). Although these parameters provided very useful insights in explaining ecologically friendly behaviour, they were often criticized as being difficult to measure and implement (Brooker, 1976;Balderjahn, 1988;Chan, 1999;Kilbourne & Pickett, 2008).…”
Section: Previous Researchmentioning
confidence: 99%